Peningkatan Kompetensi Guru Melalui Pelatihan Media Pembelajaran Interaktif Berbasis Videoscribe bagi Guru MGMP Fisika Kabupaten Lebak - Indica Yona Okyranida; Irnin Agustina Dwi Astuti (Jurnal Pengabdian Pada Masyarakat, 2020)
IMPROVING TEACHER COMPETENCE THROUGH TRAINING ON VIDEOSCRIBE-BASED INTERACTIVE LEARNING MEDIA FOR TEACHERS OF PHYSICS MGMP IN LEBAK REGENCY. The purpose of this community service is to increase the role of MGMP physics teacher in Lebak District in developing interactive learning media innovation. Media Innovation learning the form of learning media based Videoscribe. The weakness of teachers in making media learning makes a problem to be sought solution. One of the developments in science and technology that can be utilized as an effective and efficient learning media in physics learning is by making interactive learning media based Videoscribe. The method of public service is conducted by interview, observation, socialization, and training. Community service activities in the MGMP Physics district Lebak goes well according to the results of the questionnaire feedback the level of satisfaction of partners in the implementation of devotion to the community who said that partners respond to positive response (95%) With this devotion activity. This activity adds teachers’ skills to create an interactive and innovative learning medium for preparing teaching materials in schools. Media-based Videoscribe learning is one of the latest innovations for teachers in the MGMP Physics of Lebak district.